Janez Krstnik Mesar: Portrait of the Tonkin missionary from the 18th century - Šmitek, Zmago (Two Homelands, 1994)
The activities of J. K. Mesar in China and Vietnam represent a significant episode in the history of the Slovenes’ contacts with foreign cultures. As a Jesuit missionary in the first half of the 18th century, Mesar was involved in the disputes over the adaptation methods and the Portuguese patronage in China. He ended his life as the victim of the struggle between European pro-zealotry and Asian traditionalism. His biography which was reconstructed mainly on the basis of archive sources vacillates between his personal life story and the legend of him as a saint.